Type and Quantity of Shipborne Garbage at Selected Tropical Beaches - Mobilik, Julyus-Melvin; Ling, Teck Yee; Mohd Lokman, Husain; Ruhana, Hassan (Hindawi Publishing, 2016)
Marine debris is widely distributed at the coastal area of the global oceans; however, shipborne garbage source studies are still lacking to document the pollution in Malaysia TerritorialWater.Thus, this study has adopted a standard method of beach marine debris survey at five beaches and inspected 115 vessels to assess the type and amount of debris from shipping source stranded on the beach.This study found that vessel visitingMalaysian ports observed theMARPOL 73/78 Annex V requirements; however, identified objects fromshipping activity (1.3%; 2 items/km) found on the beaches indicate that there are vessels disposing of garbage illegally at sea. Therefore, there is a need to promote the use of biodegradable material and introduce environmental education to increase awareness on the vessel.